High PLA2 level is correlated with glioblastoma progression via regulating DNA replication. Issue 5 (15th February 2022) - Zhang, Haiyun; Zhao, Hanwei; Wang, Hongliang; Yin, Zhongbo; Huang, Kai; Yu, Minhong
Abstract: Phospholipases A2 (PLA2) are a superfamily of enzymes, playing a critical role in the development of various human cancers. However, the mechanism of PLA2 as an oncogene in glioblastoma remains largely unknown. In this study, we explored the effects of PLA2 on glioblastoma and investigated the underlying mechanism. The results showed that PLA2 was highly expressed in glioblastoma. Patients with a high PLA2 level have low overall survival than those with low PLA2 expression. PLA2 overexpression promoted glioblastoma cell proliferation and viability and inhibited cell apoptosis by inducing cell cycle transition from G1 to S stage. Knockdown of PLA2 inhibited tumor growth in the xenograft mice model. In addition, PLA2 knockdown decreased the protein level of MCM2 and MCM5. These findings identify PLA2 as an oncogene in glioblastoma progression and provide a promising strategy to treat glioblastoma in the future.